International Research Network Initiative (IRNI) 2024: a research networking session with Asia Pacific Universities/Institutions right at our doorstep / Lim Siong Meng ... [et al.] - Lim, Siong Meng; Abd Wahab, Mohd Shahezwan; Mohd Rock, Nik Ateerah Rasheeda y; Mohd Hatta, Fazleen Haslinda; Jayasingh Chellammal, Hanish Singh; Zamery, Muhammad ‘Izzuddin; Ramasamy, Kalavathy; Jahidin, Aisyah Hasyila; Hazizul Hasan, Mizaton; Karuppannan, Mahmathi; Mohd Fauzi, Fazlin; Ahmad, Norazua; et al. (Faculty of Pharmacy, 2024)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Malaysia had the opportunity to organise and host yet again an international program entitled International Research Network Initiative (IRNI) 2024 on the 21st November 2024, 10.00 am – 2.30 pm (GMT+8). This was an initiative undertaken to intensify research collaborations between the UiTM and universities/institutions in the Asia Pacific countries.